Vibration of Shaft System in the Mixed-Flow Pump Induced by the Rotor-Stator Interaction under Partial Load Conditions - Wei Li; Leilei Ji; Weidong Shi; Yulu Wang; Ling Zhou; Xiaoping Jiang (Shock and Vibration)
In order to reveal the relationship between rotor-stator interaction-induced unsteady flow and the shaft vibration of the mixed-flow pump, PIV (particle image velocimetry) and axis orbit experiments were carried out synchronously in a mixed-flow pump under designed flow rate (1.0Qdes) and the partial load conditions (0.4Qdes and 0.2Qdes). The distribution of the relative velocity and the vorticity in the rotor-stator interaction region at a certain position of the mixed-flow pump impeller was captured; the axis orbit diagram and the time-domain diagram of shaft system were acquired as well. Besides, the waterfall diagrams of the frequency spectrum under different flow rate conditions were compared. The results show that the backflow and the flow separation phenomenon appear in the rotor-stator interaction flow field under the partial load condition, indicating the flow instability. The medium-frequency exciting force and high-frequency exciting force induced by these unstable flows resulting from the rotor-stator interaction are the main factors to intensify the shaft vibration at the power frequency. The rotor-stator interaction under partial load condition is the main reason for the deterioration of shaft system vibration. The 2X frequency also affects the axis orbit in a low level, while other frequencies have less influence on the shaft vibration. The research results can provide the reference and theory instruction for revealing the operating characteristic of mixed-flow pump when it operates under partial load conditions and to reduce or to prevent the deterioration of vibration of shaft system.